Effects of simultaneous intervention of aerobic training and berberine supplementation on AMPK and GLUT4 gene expression in the quadriceps muscle of diabetic male rats - Mahboobe Zaefarani Arani; Javad Ramezani; Saeid Naghibi (Shahid Beheshti University, 2024)
Background and Purpose: Diabetes is a metabolic disease associated with increased blood glucose. Based on the results of previous research, physical activity, and herbal supplements containing antioxidants and anti-inflammatory agents play an important role in controlling blood glucose in diabetics. GLUT4 as a glucose transporter and AMPK as an insulin-independent biological pathway play an important role in energy homeostasis in the body. This study aimed to investigate the simultaneous intervention of aerobic training and berberine supplementation on GLUT4 and AMPK gene expression in the quadriceps muscle of diabetic male rats.   Materials and Methods: In this experimental research, 35 male Wistar rats (age 8 weeks, weight 242.15±10.32 gr) were randomly divided into five groups (n=7) including healthy control, diabetic control, diabetes + berberine, diabetes + aerobic training, and diabetes + aerobic training + berberine. Diabetes was induced by one-step intraperitoneal injection of STZ (60 mg/kg). Blood glucose above 300 mg/dL meant successful induction of diabetes. The training groups performed a treadmill protocol for six weeks, five days a week, with a gradual increase in speed and time. Berberine supplementation with a dose of 50 mg per kilogram of body weight was done by gavage on all days of week and in training days one hour before training. Forty-eight hours after the last training session, rats were deeply anesthetized by intraperitoneal injection of ketamine (75 mg/kg body weight) and xylazine (10 mg/kg body weight) and quadriceps muscle tissue samples were collected. RT-PCR technique was used to measure the relative expression of GLUT4 and AMPK genes. The data were analyzed using SPSS software. One-way analysis of variance and Tukey's post hoc test were employed for between-group comparisons of the data.   Results: AMPK and GLUT4 gene expression in the quadriceps muscle of the diabetic control group was significantly decreased compared to the healthy control group (P=0.0001). Moreover, the results showed that the content of AMPK and GLUT4 gene expression in diabetes + aerobic training and diabetes + aerobic training + berberine groups increased significantly compared to the diabetic control group (P=0.0001). This increase in gene expression was higher in the diabetes + aerobic training + berberine group than in the diabetes + aerobic training group. In addition, the level of AMPK and GLUT4 gene expression in the group of diabetes + aerobic training + berberine increased significantly compared to the diabetes + berberine group (P<0.05). However, despite the increase in gene expression of these two variables in diabetes + berberine group, these changes were not statistically significant (P>0.05) when compared to the diabetic control group.   Conclusion: The simultaneous intervention of aerobic training and berberine supplementation has positive synergistic effects on AMPK and GLUT4 gene expressions in the quadriceps muscle of type 1 diabetic rats and may improve energy homeostasis in the body.